Study of chemically peculiar stars – I. High-resolution spectroscopy and K2 photometry of Am stars in the region of M44. Issue 4 (27th January 2022) - Joshi, Santosh; Trust, Otto; Semenko, E; Williams, P E; Lampens, P; De Cat, P; Vermeylen, L; Holdsworth, D L; García, R A; Mathur, S; Santos, A R G; Mkrtichian, D; et al.
ABSTRACT: We present a study based on the high-resolution spectroscopy and K2 space photometry of five chemically peculiar stars in the region of the open cluster M44. The analysis of the high-precision photometric K2 data reveals that the light variations in HD 73045 and HD 76310 are rotational in nature and caused by spots or cloud-like co-rotating structures, which are non-stationary and short-lived. The time-resolved radial velocity measurements, in combination with the K2 photometry, confirm that HD 73045 does not show any periodic variability on time-scales shorter than 1.3 d, contrary to previous reports in the literature. In addition to these new rotational variables, we discovered a new heartbeat system, HD 73619, where no pulsational signatures are seen. The spectroscopic and spectropolarimetric analyses indicate that HD 73619 belongs to the peculiar Am class, with either a weak or no magnetic field, considering the 200-G detection limit of our study. The least-squares deconvolution profiles for HD 76310 indicate a complex structure in its spectra, suggesting that this star is either part of a binary system or surrounded by a cloud shell. When placed in the Hertzsprung–Russell diagram, all studied stars are evolved from the main sequence and situated in the δ Scuti instability strip. This work is relevant for further detailed studies of chemically peculiar stars, for example on inhomogeneities (including spots) in the absence of magnetic fields and the origin of the pulsational variability in heartbeat systems.